2017
DOI: 10.1038/tp.2017.53
|View full text |Cite
|
Sign up to set email alerts
|

Corticolimbic hyper-response to emotion and glutamatergic function in people with high schizotypy: a multimodal fMRI-MRS study

Abstract: Animal models and human neuroimaging studies suggest that altered levels of glutamatergic metabolites within a corticolimbic circuit have a major role in the pathophysiology of schizophrenia. Rodent models propose that prefrontal glutamate dysfunction could lead to amygdala hyper-response to environmental stress and underlie hippocampal overdrive in schizophrenia. Here we determine whether changes in brain glutamate are present in individuals with high schizotypy (HS), which refers to the presence of schizophr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 63 publications
2
38
2
Order By: Relevance
“…Taken together, studies in SPD cohorts seem to provide more evidence for lateral temporal and frontal lobe dysfunction than they do for dysfunction in a hippocampal–striatal–midbrain circuit, although this may be because far less research has been conducted that explicitly examines the hippocampal–striatal–midbrain circuit in psychometric schizotypy/SPD populations (110113).…”
Section: Discussion: Emerging Temporal Lobe Dysfunction In Chr Populamentioning
confidence: 99%
“…Taken together, studies in SPD cohorts seem to provide more evidence for lateral temporal and frontal lobe dysfunction than they do for dysfunction in a hippocampal–striatal–midbrain circuit, although this may be because far less research has been conducted that explicitly examines the hippocampal–striatal–midbrain circuit in psychometric schizotypy/SPD populations (110113).…”
Section: Discussion: Emerging Temporal Lobe Dysfunction In Chr Populamentioning
confidence: 99%
“…The recruitment procedure has been described in detail in our recent publications in a largely overlapping sample (Modinos et al, 2017a, 2017b). Briefly, 250 healthy individuals who responded to online advertisement were prescreened with the short version of the O‐LIFE questionnaire (Mason et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…With a large body of evidence supporting shared genetic, environmental, neurobiological, and cognitive‐emotional factors between HS and psychotic disorders (Barrantes‐Vidal, Grant, & Kwapil, 2015; Ettinger, Meyhofer, Steffens, Wagner, & Koutsouleris, 2014; Kwapil & Barrantes‐Vidal, 2015; Nelson et al, 2013), the continuum model would predict that resting hippocampal perfusion is also elevated in individuals with subclinical psychotic‐like experiences. Although neuroimaging studies are yet to test this hypothesis, HS individuals show elevated hippocampal responses to a range of cognitive and emotional tasks (Bourque et al, 2017; Modinos et al, 2017b; Mohanty et al, 2005). Thus, our study sought to investigate whether hippocampal hyperperfusion is present in this group, compared to a matched group of people with low schizotypy.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we associated the connectivity paths exhibiting higher SEC with overdrive, or pathologically enhanced engagement, given that hyper‐connectivity is considered as a response to neurological disruption [Hillary et al, ], and has been observed in individuals with PTSD [Cisler et al, ; Hayes et al, ; Simmons and Matthews, ]. The use of the word “overdrive” in such a context is not new, and has been prevalent in the literature [Modinos et al, ; Reiss et al, ]. The foci were identified using whole‐brain connectivity data without imposing any priors, while the affected connectivity paths conforming to our hypothesis were restricted to those connections that were associated with the foci.…”
Section: Introductionmentioning
confidence: 99%